2011
DOI: 10.1007/s13594-011-0002-0
|View full text |Cite
|
Sign up to set email alerts
|

Does ultrafiltration have a lasting effect on the physico-chemical properties of the casein micelles?

Abstract: The objective of this work was to determine if concentration of milk using ultrafiltration (in the absence of diafiltration) affects the physico-chemical properties of the casein micelles. The milk, once concentrated, was brought back to its original concentration and the physico-chemical properties as well as its susceptibility to rennet induced gelation were assessed. Although much is understood on the renneting behavior of concentrated milk, no information is available on how (or if) ultrafiltration per se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 42 publications
11
34
0
Order By: Relevance
“…In UF process, highly significant (P \ 0.01) reduction in the pH of retentates was observed from 19 (pH 6.60) to 59 (pH 6.41) concentration (Table 1). The observed decrease in pH was in good agreement with the previously reported results (Huppertz et al 2004;Karlsson et al 2005;Ferrer et al 2011). The concentration of milk salts (Ca 2?…”
Section: Chemical Compositionsupporting
confidence: 93%
See 2 more Smart Citations
“…In UF process, highly significant (P \ 0.01) reduction in the pH of retentates was observed from 19 (pH 6.60) to 59 (pH 6.41) concentration (Table 1). The observed decrease in pH was in good agreement with the previously reported results (Huppertz et al 2004;Karlsson et al 2005;Ferrer et al 2011). The concentration of milk salts (Ca 2?…”
Section: Chemical Compositionsupporting
confidence: 93%
“…increases during UF process which changes the cationic profile of milk based on their association with proteins, but total calcium to protein ratio decreases with increase in CF due to passage of soluble calcium in permeate (Ferrer et al 2011;Sikand et al 2013). Moreover, marked decreased (P \ 0.01) in the pH of 59 Na-K was also observed which was attributed to the DF of 59 UFR sample with NaCl-KCl added RO water (Table 1).…”
Section: Chemical Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher concentration of soluble caseins was present in the supernatant of reconstituted MPC samples (lanes 2 to 9) compared to skim milk (lane 1) despite the equal initial protein content 3.2% (w/ w). It has been previously demonstrated that after membrane concentration, there is an increase in soluble caseins in both fresh or reconstituted retentates (Ferrer et al 2011;Sandra and Corredig 2013). The soluble fraction varies depending on the concentration and the presence of DF (Li et al 2015).…”
Section: Protein Composition Of the Soluble Fractionmentioning
confidence: 99%
“…Mineral equilibrium also is of importance in determining the rehydration and functional properties of MPC, such as renneting and emulsifying properties (Ferrer et al 2011;Ye 2011;Sandra and Corredig 2013). Imaging techniques such as scanning electron microscopy (SEM) and transmission electron microcopy (TEM) have been employed to study the microstructure of dairy powders in the dry state (Gaiani et al 2007;Tamime et al 2007) or after rehydration (Havea 2006;Mimouni et al 2010b).…”
Section: Introductionmentioning
confidence: 99%